Preoperative Bowel Preparation in Minimally Invasive and Vaginal Gynecologic Surgery - Michail Diakosavvas; Nikolaos Thomakos; Alexandros Psarris; Zacharias Fasoulakis; Marianna Theodora; Dimitrios Haidopoulos; Alexandros Rodolakis (The Scientific World Journal)
Bowel preparation traditionally refers to the removal of bowel contents via mechanical cleansing measures. Although it has been a common practice for more than 70 years, its use is based mostly on expert opinion rather than solid evidence. Mechanical bowel preparation in minimally invasive and vaginal gynecologic surgery is strongly debated, since many studies have not confirmed its effectiveness, neither in reducing postoperative infectious morbidity nor in improving surgeons’ performance. A comprehensive search of Medline/PubMed and the Cochrane Library Database was conducted, for related articles up to June 2019, including terms such as “mechanical bowel preparation,” “vaginal surgery,” “minimally invasive,” and “gynecology.” We aimed to determine the best practice regarding bowel preparation before these surgical approaches. In previous studies, bowel preparation was evaluated only via mechanical measures. The identified randomized trials in laparoscopic approach and in vaginal surgery were 8 and 4, respectively. Most of them compare different types of preparation, with patients being separated into groups of oral laxatives, rectal measures (enema), low residue diet, and fasting. The outcomes of interest are the quality of the surgical field, postoperative infectious complications, length of hospital stay, and patients’ comfort during the whole procedure. The results are almost identical regardless of the procedure’s type. Routine administration of bowel preparation seems to offer no advantage to any of the objectives mentioned above. Taking into consideration the fact that in most gynecologic cases there is minimal probability of bowel intraluminal entry and, thus, low surgical site infection rates, most scientific societies have issued guidelines against the use of any bowel preparation regimen before laparoscopic or vaginal surgery. Nonetheless, surgeons still do not use a specific pattern and continue ordering them. However, according to recent evidence, preoperative bowel preparation of any type should be omitted prior to minimally invasive and vaginal gynecologic surgeries.